2007
DOI: 10.1111/j.1538-7836.2007.02320.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant activated factor VII efficacy and safety in a model of bleeding and thrombosis in hypothermic rabbits: a blind study

Abstract: To cite this article: Godier A, Mazoyer E, Cymbalista F, Cupa M, Samama C-M. Recombinant activated factor VII efficacy and safety in a model of bleeding and thrombosis in hypothermic rabbits: a blind study. J Thromb Haemost 2007; 5: 244-9.See also Levi M. Recombinant factor VIIa and trauma: treatment that does not leave you in the cold. This issue, pp 242-3.Summary. Background: Recombinant activated factor VII (rFVIIa) is increasingly used to secure hemostasis in hemorrhagic situations in trauma and surgical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…We developed a new rabbit model of instantaneous, reversible, calibrated supra-AS, adapted from Assad et al 16 and Godier et al 17 (see Methods in the Online Data Supplement). This model allowed the evaluation in the same rabbit, of the dynamic time course of loss and recovery of HMW multimers.…”
Section: Instantaneous Induction and Reversion Of High Shear Stress Imentioning
confidence: 99%
“…We developed a new rabbit model of instantaneous, reversible, calibrated supra-AS, adapted from Assad et al 16 and Godier et al 17 (see Methods in the Online Data Supplement). This model allowed the evaluation in the same rabbit, of the dynamic time course of loss and recovery of HMW multimers.…”
Section: Instantaneous Induction and Reversion Of High Shear Stress Imentioning
confidence: 99%
“…This could also be demonstrated in animal studies. 34,35 An accumulation of more than 1 of these factors led to a failure of rFVIIa therapy. This observation was also reported in large trauma trials.…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, it was found that rFVIIa increased the thrombosis rate in a rabbit model of carotid artery injury without reducing bleeding from standardized hepatic and splenic lesions, despite a hypercoagulable state as evidenced by TEG [59]. In a rabbit model of bleeding and thrombosis of the carotid artery, rFVIIa administration decreased bleeding time in both hypothermic or normothermic animals [60]. In 2008, Zhang et al [61] reported that rFVIIa treatment after traumatic brain injury (TBI) in a pig model reduced expansion of hemorrhagic cerebral contusion volume without exacerbating the severity of microclot formation and provided some neuroprotective effect.…”
Section: Insights From Basic Sciencementioning
confidence: 98%